Letter (copy) : International Brigade - Citrine, Walter, 1887-1983
034-0147-001 International WMC/WJB/AC/10 14th September, 1938. Mrs. Charlotte Haldane, International Brigade Dependants & Wounded Aid Committee, 1, Litchfield Street, W.C.2. Dear Mrs. Haldane, INTERNATIONAL BRIGADE. We duly received your letter of 12th instant, in which you refer to the amount of £5,000 that the General Council have donated to the International Solidarity Fund, and request consideration of the possibility of allotting a portion of that sum to your Committee. We may say that we have already started using the money to purchase foodstuffs, as these are urgently required. It is only too true, as was said at the Congress, that many of the workers in Spain and their families are now suffering hunger. It will take much more than £5,000 to send supplies which will be adequate, and another appeal for funds has had to be made. We write this with reluctance, as we well understand how pressing is the need also for help to be given to your Committee. However, while we are not very hopeful that we shall be in a position to make any grant (quite apart from the question of the strict purpose for which money is being subscribed to us, namely, for the relief of the Spanish workers) we will submit your request to the Council. In the meantime, it would help us if we could receive a copy of your latest balance-sheet, together with the information as to the number of persons being assisted by your Committee, and especially the names of the trade unionists (and their organisations) and Labour Party members included among them. Yours faithfully, General Secretary. 292/946/34/147